Nitrogen Addition Increases the Sensitivity of Photosynthesis to Drought and Re-watering Differentially in C3 Versus C4 Grass Species - Zhong, Shangzhi; Xu, Yueqiao; Meng, Bo; Loik, Michael E.; Ma, Jian-Ying; Sun, Wei (Frontiers in Plant Science, 2019)
Global change factors, such as variation in precipitation regimes and nitrogen (N) deposition, are likely to occur simultaneously and may have profound impacts on the relative abundance of grasses differing in functional traits, such as C3 and C4 species. We conducted an extreme drought and re-watering experiment to understand differences in the resistance and recovery abilities of C3 and C4 grasses under different N deposition scenarios. A C3 perennial grass (Leymus chinensis) and two C4 grasses (annual species Chloris virgata and perennial species Hemarthria altissima) that co-occur in Northeast China were selected as experimental plants. For both C3 and C4 grasses, Nitrogen addition caused a strong increase in biomass and resulted in more severe drought stress, leading to a change in the dominant photosynthetic limitation during the drought periods. Although N addition increased antioxidant enzyme activities and protective solute concentrations, the carbon fixing capacity did not fully recover to pre-drought levels by the end of the re-watering period. N addition resulted in lower resilience under the drought conditions and lower resistance at the end of the re-watering. However, N addition led to faster recovery of photosynthesis, especially in the C3 grass, which indicate that the effect of N addition on photosynthesis during drought was asymmetric, especially in the plants with different photosynthetic nitrogen use efficiency. These findings demonstrated that nitrogen deposition may significant alter the susceptibility of C3 and C4 grass species to drought stress and re-watering, highlighting the asymmetry to improve our understanding about plant responses to climate change.